2016
DOI: 10.1177/0192513x16647985
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Shaken Baby Syndrome: Evaluation of a Multiple-Setting Program

Abstract: Abusive head trauma, including shaken baby syndrome, is a serious form of abuse that often results in lifelong developmental challenges or infant death. Educational programs have helped reduce the number of infants hospitalized due to abusive head trauma. The current study provides a process evaluation of Prevent Child Abuse Tennessee's Shaken Baby Prevention Project. We utilized survey data from (a) 189 trained professionals who delivered the program to new parents in either the hospital or home-visiting sett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…Additionally, Altman et al (2011) and Dias et al (2005) observed reductions in SBS cases after the implementation of SBS prevention programs in their respective regions (Altman et al, 2011;Dias et al, 2005). According to other parallel studies, parent education programs that inform parents about the dangers of shaking infants and provide them with coping skills to deal with the stresses of caregiving help reduce the number of children presenting with SBS (McInerney et al, 2020;Reese et al, 2014;Stolz et al, 2017) The incidence of SBS in Turkey remains unknown (Taşar et al, 2014). Although studies on this subject are very limited in Turkey, the knowledge level of caregivers appears to be insufficient (Akcay Didisen et al, 2019;Cansever et al, 2012;Meral et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Additionally, Altman et al (2011) and Dias et al (2005) observed reductions in SBS cases after the implementation of SBS prevention programs in their respective regions (Altman et al, 2011;Dias et al, 2005). According to other parallel studies, parent education programs that inform parents about the dangers of shaking infants and provide them with coping skills to deal with the stresses of caregiving help reduce the number of children presenting with SBS (McInerney et al, 2020;Reese et al, 2014;Stolz et al, 2017) The incidence of SBS in Turkey remains unknown (Taşar et al, 2014). Although studies on this subject are very limited in Turkey, the knowledge level of caregivers appears to be insufficient (Akcay Didisen et al, 2019;Cansever et al, 2012;Meral et al, 2018).…”
Section: Discussionmentioning
confidence: 94%
“…As such, there is a clear need to equip caregivers with an understanding of when and why babies cry as well as how they should respond to crying. Evidence suggests that individuals can be educated on the dangers of shaking an infant (Chen et al, 2019; Fujiwara, 2015; Fujiwara et al, 2020; Lopez‐Bushnell et al, 2017; Reese et al, 2014; Sayed & Mahmoud, 2020; Stolz et al, 2017). In the program planned by the “Shaken Baby Syndrome National Center,” it was reported that nonaccidental head trauma decreased by 47% over 3 years in New York after providing information about SBS in hospital to all parents with newborn babies (Centers for Disease Control and Prevention, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…While studies of programmes in this category made up the majority of the articles included in this review, it appears that parent education programmes show mixed promise in their effectiveness for reducing the incidence of AHT at this time; albeit some of these programmes did change parent behaviour related to the infant's crying. The studies included in this review that fall under this category can be easily subdivided again into three groups: (i) studies referring to various aspects of a programme called Period of PURPLE Crying® (PPC) (Barr et al ., 2009a, 2009b, 2015, 2018; Fujiwara et al ., 2012; Fujiwara, 2015; Mirabal Rodríguez et al ., 2011; Ornstein et al ., 2016; Stolz et al ., 2017; Zolotor et al ., 2015); (ii) studies referring to programmes of parent newborn education in hospitals after the birth of a child, exemplified by Dias (Altman et al ., 2011; Bravo, 2014; Dias et al ., 2005, 2017; Duzinski et al ., 2018; Keenan & Leventhal, 2010; Kelly et al ., 2016; Palusci et al ., 2006; Trossman, 2016); and (iii) studies about other parent education programmes as a method to prevent AHT (Bechtel et al ., 2011; Coster, 2017; Deyo et al ., 2008; Eismann et al ., 2019; Lopes et al ., 2018; Morrill et al ., 2015; Rabbitt et al ., 2018; Russell et al ., 2008; Russell, 2010; Simonnet et al ., 2014; Taşar et al ., 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Among them, parental education about infant crying and risks of shaking a baby stood out for its empirical evidence. Stolz et al (2017) found that Shaken Baby Syndrome training provided in both the home and hospital setting was effective and well-received. Taking a broader view, the U.S. Centers for Disease Control and Prevention (Fortson et al 2016) recommends forming community-level strategies to modify negative community influences and change cultural norms through laws that effect parenting.…”
Section: Addressing Abusive Head Traumamentioning
confidence: 95%